Filsafat Dan Iman: Memahami Kebenaran Mutlak Dalam Teologi Kristen - Riawan Riawan; Mozes Lawalata (LPPM - STT Kadesi Bogor, 2024)
The concept of absolute truth holds a central role in the Christian tradition. This truth is believed to originate from the word of God revealed in the Bible and His self-revelation through Jesus Christ. From the beginning, there have been efforts to reconcile revealed truth with rational philosophical thought. This article explores the relationship between philosophy and faith in understanding absolute truth according to Christian theology. By examining the thoughts of eminent philosophers and theologians such as Augustine and Aquinas, it discusses how reason can be combined with faith to attain a more comprehensive understanding. Epistemological methods and logical reasoning are employed to study the concept of truth in the Bible and church teachings. Nevertheless, absolute truth remains centered on divine revelation that transcends reason alone. The article also delves into the implications of absolute truth on Christian doctrine, worship, and conduct, as well as the challenges posed by relativism and pluralism. Ultimately, it discusses efforts to reconcile faith and reason, and the defense of absolute truth using rational arguments while maintaining humility. By combining these two aspects, Christians can gain a more comprehensive grasp of the ultimate truth that emanates from God.